Ecoturismo, alternativa de desarrollo socioeconómico en la comunidad nativa de Yurilamas, en la cuenca del Alto Shanusi – provincia de Lamas - Cotrina Trigozo, Tomas (2006)
For the last two decades, we have consolidate the lntemational request for very diverses products of nature tourism, being notable the impulse that they have charged the most variated way of eco - tourism, which many of them have developed around t e nature areas. This has given rise to as much the inversions as local communities to see economic chances in this kind of tourism that many times are not consequentences with the maintenancing of natural and cultural resources. On this searching is considerated as an important issue to the eco - tourism as a choice for the development socio - economic this searching is reaching for a choice for the use of this zone through this kind of tourism as well as using it as a tool for enhancing the living quality of the people who live there. this searching project basically is the effort of the people as well as of our person for creating a choice of development denominated eco - tourism which allow us to reach its maximum social - tourism which allow us to reach its maximum social- economic development that is based on this searching project. Consequently we have started by recognizing the natural and cultural importance that remains the alto shanussi basin, as well as the appropriated use that it would have in the future the altogether cooperating of the people who live there. Is like this how we did an investigation of the natural and cultural rich potential with the only purpose of showing that it's being established a potential eco - tourism always defining its key parameters of sustainability. its also rebounded the economics kindness' that would give origin to the eco - tourism like a-eating of employments spots and the barrowing of service such as feeding, rural convivence, guiding, that would give supportable and equalities entries the community and for many character actors as much as possible, including the private touristic operators.